Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.gene.2011.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Self-assemble gene delivery system for molecular targeting using nucleic acid aptamer

Abstract: We have developed a novel vector constructed with pDNA, polyethylenimine (PEI), and mucin 1 (MUC1) aptamer for tumor-targeted gene delivery. The MUC1 aptamer and non-specific aptamer were employed to coat the pDNA/PEI complexes electrostatically and stable nanoparticles were formed. The addition of a non-specific aptamer to the pDNA/PEI complex decreased gene expression in the human lung cancer cell line, A549 cells expressing MUC1 regularly. At the same time, the pDNA/PEI/MUC1 aptamer complex showed higher ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 25 publications
(17 reference statements)
1
34
0
Order By: Relevance
“…The highest level of luciferase expression was seen for APT–PEI–pDNA in MUC1+ cells, with a significant difference observed between targeted and nontargeted NPs. The in vitro results were confirmed with an in vivo study, which showed significant gene expression in mice treated with APT–PEI–pDNA as compared with PEI–pDNA scrambled aptamer complexes and PEI–pDNA . Another study by Arias and co‐workers used S2.2 and 5TR aptamers for targeted gene delivery by an elastin‐like recombinamer (ELR) vector .…”
Section: The Muc1 Aptamer In Targeted Drug Deliverymentioning
confidence: 63%
See 1 more Smart Citation
“…The highest level of luciferase expression was seen for APT–PEI–pDNA in MUC1+ cells, with a significant difference observed between targeted and nontargeted NPs. The in vitro results were confirmed with an in vivo study, which showed significant gene expression in mice treated with APT–PEI–pDNA as compared with PEI–pDNA scrambled aptamer complexes and PEI–pDNA . Another study by Arias and co‐workers used S2.2 and 5TR aptamers for targeted gene delivery by an elastin‐like recombinamer (ELR) vector .…”
Section: The Muc1 Aptamer In Targeted Drug Deliverymentioning
confidence: 63%
“…However, a comparison between the MUC1 aptamer‐conjugated NPs and anti‐MUC1 antibody is required to extract a better conclusion. Moreover, few reports have employed random ssDNA NPs as negative controls in targeting studies with MUC1 . Since ssDNA may attach accidentally to the cell surface, we suggest that all future experiments should include this configuration as a negative control.…”
Section: Resultsmentioning
confidence: 99%
“…This approach enhanced the stability features of targeting 297 systems, in addition to the selective drug delivery to PMSA positive cancer cells [122]. under in vitro and in vivo conditions than previous ones [129]. activity on cancer cells [130].…”
mentioning
confidence: 96%
“…Aptamers as targeting agents could conduct the therapeutic carrier to the 127 specific site of action and therefore, restrict biodistribution of active pharmaceutical ingredients 128 and eliminate adverse effects [44,45]. 129 Nanostructures as a drug carrier can be designed to target specifc cells and tissues and deliver the 130 drug in a stimuli-responsive manner. Up to now, a wide range of nanocariers have been 131 and feasibility of variable routes of administration, including oral application and inhalation.…”
mentioning
confidence: 99%
“…Several recent studies have reported the application of anti-MUC1 apt as a ligand for nanoparticles to specifically target various epithelial cancer cells. [5][6][7] Dendrimers are highly compact nanostructures composed of numerous branched layers and have consequently been studied in great detail as potential carriers for the development of drug delivery systems. 8) Good safety and target cell-specificity are important properties for the successful development of drug delivery systems based on dendrimers.…”
mentioning
confidence: 99%